Effects of Silica Addition and Alkaline Surface Treatment of Kenaf Fibre on Mechanical Properties of Hybrid Epoxy/Silica/Kenaf Composites using Hand Lay-up Method - Ismail Zainol (Tanjong Malim, 2019)
Effects of Silica Addition and Alkaline Surface Treatment of Kenaf Fibre on Mechanical Properties of Hybrid Epoxy/Silica/Kenaf Composites using Hand Lay-up Method by Ismail Zainol